PRODUKSI DAN KUALITAS PRODUKSI BUAH TOMAT YANG DIBERI BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR - Wijaya, Agus Sunar; Sangadji, Muhd. Nur; Muhardi, Muhardi (AGROTEKBIS, 2017)
This research consisted of two stages, the first aimed to determine the best type of liquid organic fertilizer which can be used in the fertilization of tomato plants andthe second aimed to determine the best concentration of liquid organic fertilizer which can be applied to tomato plants. This research purpose was to investigate the response of tomato plant (Solanum licopersicum Mill.) as shown byitsyield and quality.Â  This research used a Randomized Completely Block design in which seventreatmentsof different concentrations and two types of liquid organic fertilizers were applied.Â  The treatments significantly affected the number of tomato fruits but not on their weight and diameter as well as the content of C vitamin. Best yield and quality of the tomatoes was found in the gremont liquid organic fertilizer at the concentration of 2.4 ml/80 ml water.Keywords: Liquid organic fertilizer, Quality and Yield of tomato.